A crime 2.0: Cybercrime, e-talent, and institutions - Seo-Young Cho (Philipps-University Marburg, School of Business and Economics, 2016)
Cybercrime is typically profiled as a skill-intensive crime committed by educated, young criminals. This observation raises the controversial question of whether advanced knowledge and skills are a pull factor of cybercrime. In this paper, the linkage between e-skills and cybercrime is investigated using statistics from up to 28 European countries. Through the investigation, it is shown that electronic skills induce more cybercrime under weak institutions where the rules of law do not provide protection and incentives for productive entrepreneurial activities. This compound effect between e-skills and institutions suggests that institutional factors are crucial to allocating human capital between productive and criminal activities in cyberspace.
Keywords: E24; K42; O15; 330; cybercrime; e-skills; institutions; entrepreneurship